The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15649/cuidarte.1092
|View full text |Cite
|
Sign up to set email alerts
|

Correlación del grado de percepción y cultura de seguridad del paciente en una Institución de tercer nivel 2015-2019

Abstract: Introducción: La seguridad del paciente es considerado como un patrón integrado de comportamiento individual y organizacional, basado en creencias y valores compartidos que continuamente busca minimizar el daño al paciente, que resulta de la atención. Objetivo: Analizar la correlación de percepción de cultura de seguridad del paciente, y grado de seguridad percibido en funcionarios de una Institución de Salud de tercer nivel de atención (2015-2017-2019). Materiales y Métodos: Estudio cuantitativo correlacional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…The review included 30 studies from five Latin American countries: 22 studies in Brazil [ 88 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ], 3 studies in Mexico [ 112 , 113 , 114 ], 3 studies in Colombia [ 115 , 116 , 117 ], 1 study in Peru [ 67 ], and 1 study in Argentina [ 118 ]. All studies reported data from the HSOPSC 1.0; none reported data from the HSOPSC 2.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review included 30 studies from five Latin American countries: 22 studies in Brazil [ 88 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ], 3 studies in Mexico [ 112 , 113 , 114 ], 3 studies in Colombia [ 115 , 116 , 117 ], 1 study in Peru [ 67 ], and 1 study in Argentina [ 118 ]. All studies reported data from the HSOPSC 1.0; none reported data from the HSOPSC 2.0.…”
Section: Resultsmentioning
confidence: 99%
“…For example, most studies (n = 28) were conducted by researchers at hospitals, but one was conducted by a professional association [ 114 ] and another during an academic event [ 67 ]. In 25 studies, the surveys were delivered physically, but 5 were delivered online [ 67 , 95 , 113 , 114 , 117 ]. The majority of the studies (n = 17) included staff participation from more than one hospital service, including administrative staff and medical residents.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review by Camacho-Rodriguez et al, 9 confirmed the global concern about the PSC in Latin America, revealing that only 30 studies, limited only to five countries (none from Central America), reported a PSC evaluation. Most of these studies are from Brazil (22 studies), and only three and one from Colombia [39][40][41] and Argentina, 42 respectively. However, no Chilean studies have assessed PSC.…”
Section: Benchmarking In Latin American Settingsmentioning
confidence: 99%
“…The descriptive results of this study consider the focus on a highly complex hospital, with the participation of a majority of female nurses with work experience of fewer than five years, similar to research developed in Colombia [ 26 ] and Brazil [ 27 ]. Most of the participants in this research were in an age range of 19 to 63 years old and worked more than 40 h a week, which aligns with another study in Minas Gerais, Brazil [ 28 ].…”
Section: Discussionmentioning
confidence: 92%